JAK kinase inhibitors for the treatment of acute lymphoblastic leukemia - Degryse, Sandrine (J Hematol Oncol, 2015)
Recent studies of acute lymphoblastic leukemia have identified activating mutations in components of the interleukin-7 receptor complex (IL7R, JAK1, and JAK3). It will be of interest to investigate both JAK1 and JAK3 kinase inhibitors as targeted agents for these leukemias.